Bacteria in the dust of rooms - McDonald, Vera Alta (My University, 1904)
Introduction: Bacteria are found every-where in nature, except at very high altitudes and at great depths. Among these various places, the dust of the air contains a great number of these minute microscopic organizations. Furthermore, these micro-organisms are very apt to be found clinging singly or in clusters to the larger or smaller particles of one kind or another, which usually make up the bulk of visible or invisible dust in inhabited regions. It is well known that there are certain occupations which confine persons to closed rooms or places in which dust particles of one kind or another are very abundant. Thus day after day, persons confined in air charged with coal-dust, metallic dust, cotton, woolen, or tobacco dust, are subject to attacks of more or less well marked pulmonary affections. There are three prominent forms of the living elements of dust, or the minute vegetable organisms, called bacteria, yeasts, and molds. Among these, the bacteria are far the most important; most of them being harmless to man and serving a very important purpose in the economy of nature in tearing asunder dead and worn out organic material and setting it free in suitable condition for the building up of new forms of life. A few species of bacteria however, are capable of causing some of the most wide-spread and dreaded of human diseases.
Citation: McDonald, Vera Alta. Bacteria in the dust of rooms. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Bacteria; Rooms; Pathogens; Theses